2019
DOI: 10.1038/s41598-019-40399-8
|View full text |Cite|
|
Sign up to set email alerts
|

The genetic legacy of continental scale admixture in Indian Austroasiatic speakers

Abstract: Surrounded by speakers of Indo-European, Dravidian and Tibeto-Burman languages, around 11 million Munda (a branch of Austroasiatic language family) speakers live in the densely populated and genetically diverse South Asia. Their genetic makeup holds components characteristic of South Asians as well as Southeast Asians. The admixture time between these components has been previously estimated on the basis of archaeology, linguistics and uniparental markers. Using genome-wide genotype data of 102 Munda speakers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 43 publications
11
42
0
Order By: Relevance
“…The admixture between local South Asians and incoming Southeast Asians took place ~2000-3800 years ago giving rise to the AAA ancestry. Notably, the South Asian population(s) with whom the incoming Southeast Asians mingled were AASI related with little to no West Eurasian ancestry fraction [27]. Finally, it has been showed that the Tibeto-Burmans (ATBs) derived their ancestry through admixture with low-altitude East Asians who migrated from China and likely across Northern India or Myanmar [28] leading to the high genomic proximity between South Asians of ATB ancestry and East Asians.…”
Section: South Asians: a Variegated Canvas For Covid-19mentioning
confidence: 99%
“…The admixture between local South Asians and incoming Southeast Asians took place ~2000-3800 years ago giving rise to the AAA ancestry. Notably, the South Asian population(s) with whom the incoming Southeast Asians mingled were AASI related with little to no West Eurasian ancestry fraction [27]. Finally, it has been showed that the Tibeto-Burmans (ATBs) derived their ancestry through admixture with low-altitude East Asians who migrated from China and likely across Northern India or Myanmar [28] leading to the high genomic proximity between South Asians of ATB ancestry and East Asians.…”
Section: South Asians: a Variegated Canvas For Covid-19mentioning
confidence: 99%
“…8,14 With the technological advancement, a much clearer picture has now emerged, showing a strong association of largely male mediated gene flow for the dispersal of Mundari speakers from Southeast Asia to South Asia. [14][15][16] The autosomal data showed a bidirectional geneflow between South and Southeast Asia. 14 In a recent genome-wide study of a large number of South and Southeast Asian populations, Dravidian speakers of Kerala and Lao speakers from Laos were found to be the best ancestral proxies for Mundari speakers.…”
Section: Introductionmentioning
confidence: 99%
“…14 In a recent genome-wide study of a large number of South and Southeast Asian populations, Dravidian speakers of Kerala and Lao speakers from Laos were found to be the best ancestral proxies for Mundari speakers. 15 The admixture dates for these ancestries were estimated to be between 2-3.8 kya. Moreover, this study also found clearcut genetic differentiation between North and South Munda groups 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations